2020
DOI: 10.1002/gsj.1390
|View full text |Cite
|
Sign up to set email alerts
|

The pressure behind corporate social performance: Ownership and institutional configurations

Abstract: Research summary Drawing on the “varieties of capitalism” literature, we develop an actor‐centered framework that explains firm‐level corporate social performance (CSP) by emphasizing the importance of considering owners' and other stakeholders' motives toward CSP—which can be instrumental, relational or moral—and their salience in the national institutional setting. Results from an international panel show that investment company (government) ownership has a stronger negative (positive) relationship with CSP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 109 publications
3
29
0
Order By: Relevance
“…Thus, more multi-country examinations of the effects of ownership may shed light on the influence of ownership on sustainability. In this vein, the examination of ownership structures of corporations where owners from different countries (with often different institutional settings) hold stakes may add to our understanding of how firm goals and behavior are affected by the co-existence and interaction of owners of different types and from different countries (e.g., Desender & Epure, 2020;Dyck et al, 2019;Kavadis & Castañer, 2014, 2015.…”
Section: Geographic Scope (Countries)mentioning
confidence: 99%
“…Thus, more multi-country examinations of the effects of ownership may shed light on the influence of ownership on sustainability. In this vein, the examination of ownership structures of corporations where owners from different countries (with often different institutional settings) hold stakes may add to our understanding of how firm goals and behavior are affected by the co-existence and interaction of owners of different types and from different countries (e.g., Desender & Epure, 2020;Dyck et al, 2019;Kavadis & Castañer, 2014, 2015.…”
Section: Geographic Scope (Countries)mentioning
confidence: 99%
“…One apparent gap deriving from our review is that most of the studies do not link institution-level and firm-level governance factors to examine how stakeholder-oriented CG practices are adopted at the firm level. Rare exceptions are the study by Essen et al (2013), which examines how the strength of labour institutions positively affects the effectiveness of blockholder ownership in Europe and the study by Desender and Epure (2020). The latter shows that ownership structures such as block holdings and government holdings have stronger effects on corporate social performance in liberal market economies than in coordinated market economies.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have found a negative relationship between family firm ownership and CSR performance [67,87,99,100], such as ESG (environmental, social, and governance) performance [20,[101][102][103]. One explanation is that family owners have invested their private wealth into the firm and have both economic and personal motives to run the firm [101,104,105].…”
Section: Ownership Reducing Csrmentioning
confidence: 99%
“…Finally, Desender and Epure [100] examined the effect of investment company ownership and government ownership on CSR and found that investment company ownership reduces, whereas government ownership increases corporate social performance more in liberal market economies than in coordinated market economies, which counterbalance the interests of multiple stakeholders.…”
Section: Contingent Factors For the Relationship Between Family Firm ...mentioning
confidence: 99%